Ethical violation by the Chairman of the Constitutional Court against Indonesian law and democracy - Resopijani, A.; Neonbeni, Yohanes Baptista (Dynamics of Politics and Democracy, 2023)
Purpose: This study analyzes the decision of the Honorary Council of the Constitutional Court Number 02/MKMK/L/11/2023 regarding ethical violations by the Chairman of the Constitutional Court. The Constitutional Court's ruling on the age limit for presidential and vice-presidential candidates sparked public debate and raised concerns about democratic principles in Indonesia. Method: This research uses normative legal methods focusing on coherence among legal principles, concepts, and applicable rules. Results: The findings show that Anwar Usman was proven to have seriously violated the code of ethics and behavior of constitutional judges. In a state governed by law, rulers and citizens are equal before the law. Judges must not abuse their authority for personal or group interests. The MKMK decision seeks to uphold judicial ethics and restore public trust in the Constitutional Court. Conclusion: The findings confirm that violations of judicial ethics at the highest level of the Constitutional Court undermine the principles of impartiality and democracy. The MKMK's decision provides a legal and moral corrective that reaffirms the importance of integrity and judicial independence, with the aim of restoring institutional legitimacy ahead of the 2024 general elections. Limitations: This research is limited to analyzing MKMK Decision Number 02/MKMK/L/11/2023 and the applicable judicial code of ethics. Contributions: The study contributes to strengthening judicial accountability, offers insights for legal scholars, and supports public confidence in constitutional justice.